Heteropsis (Nymphalidae: Satyrinae: Satyrini: Mycalesina): 19 new species from Madagascar and interim revision - Lees, David C. (Zootaxa, 2016)
The genus Heteropsis Westwood, 1850 is monophyletic and contains the most diverse evolutionary radiation of butterflies in the Malagasy Region, with 46 up to now known species (53 accepted taxa) and at least 23 undescribed species in collections to date. Mixed species in historical descriptions and lost types in this genus have hindered taxonomic progress until now. A lectotype female is thus designated for the only surviving syntype that can be found for Mycalesis andravahana Mabille, 1878. Mycalesis difficilis Mabille, 1880 and three names of Oberthür, 1916 lectotypified here, Henotesia undulosa, Henotesia undulosa var. luctuosa and Henotesia andravahana var. macrophthalma, newly become its synonyms. A lectotype is also specified for Gallienia alaokola Oberthür, 1916. These acts now clarify potential confusion among the minimum of five species that these two nominal taxa represent, and thus facilitate description of related species compromised by the original descriptions (for one of which, the name Henotesia andravahana ab. marmorata Aurivillius, 1925 is unavailable). To solidify description of similar species, lectotypes are also designated for the following nominal species of Oberthür, 1916: Culapa comorana, C. pauper, Culapa (“var. ou espèce séparée”) pseudonarcissus, C. laeta, C. laetifica, C. anceps, C. undulata, C. turbans, C. curvatula, C. ornata, C. pallida, and of Oberthür, 1923: C. houlbertiana, and also for Mycalesis iboina Ward, 1870, M. strigula Mabille, 1877, M. maeva Mabille, 1878, M. ankoma Mabille, 1878, M. irrorata Mabille, 1880 and M. butleri Mabille, 1880. The following 19 new species are described within Heteropsis from Madagascar, which are organised within species groups that are briefly characterised and discussed: in the Ht. exocellata group, Heteropsis mimetica Lees & Kremen, sp. nov.; in the Ht. antahala group, Heteropsis hazovola Lees & Raharitsimba, sp. nov.; in the Ht. drepana group, Heteropsis harveyi Lees & Kremen, sp. nov.; Heteropsis vanewrighti Lees, sp. nov.; Heteropsis westwoodi Lees, sp. nov., Heteropsis pauliani Lees, sp. nov.; Heteropsis imerina Lees, sp. nov.; in the Ht. subsimilis group, Heteropsis kremenae Lees, sp. nov.; Heteropsis avaratra Lees & Kremen, sp. nov. Heteropsis sogai Lees, sp. nov., and in the Ht. strigula group, Heteropsis tornado Lees, Allaoui & Aduse-Poku, sp. nov., Heteropsis lanyvary Lees, sp. nov.; Heteropsis barbarae Lees & Kremen, sp. nov.; Heteropsis menamenoides Lees, sp. nov.; Heteropsis roussettae Lees & Kremen, sp. nov.; Heteropsis tianae Lees & Kremen, sp. nov.; Heteropsis oberthueri Lees, sp. nov.; Heteropsis borgo Lees, sp. nov. and Heteropsis vertigo Lees & Raharitsimba, sp. nov. Counting the resulting synonymy of Heteropsis difficilis (Mabille, 1880), with Ht. andravahana (Mabille, 1878), this brings the Malagasy Heteropsis fauna to 64 species, about 2/3 of which are here revised.